Long Run Potential Gains of Portfolio Diversification across United State, Japan, China, Singapore, and Malaysia - Chee, Chong Meng (2010)
This study investigates the long run relationship among assets from common three types of common capital market and across five countries. Malaysian major trading partners (US, Japan, China and Singapore) are chosen to be studied. The research main concern is to identify the absence of long run comovement among assets to ensure long run potential gains of diversification effort by using both Johansen bivariate and multivariate approaches. Previous empirical researches have devoted substantial endeavour only on particular single asset class or market and is tested across nations, while this study extend to various domestic and foreign asset classes. To fulfill the main objective of the study, four different levels of potential diversification are separately studied such as sectoral, domestic market-varied, international market and international portfolio, with a sample of daily data that covers roughly from 1999 to 2006. Majority of the multivariate findings of this study support capital market integration and limits long term benefits of portfolio diversification. Particular, five national portfolio returns subject to identical risk factors that leads them to move interdependently. However, bivariate findings appear that some combinations of two assets are significantly offer more chance and opportunity for beneficial long run diversification.